Practical efficacy and safety of Konsilar D24 in patients with hypertension: data from the KONSONANS program - A. O. Konradi; A. S. Galyavich; V. V. Kashtalap; Yu. M. Lopatin; N. P. Lyamina; S. V. Nedogoda; A. O. Nedoshivin; G. I. Nechaeva; L. G. Ratova; I. I. Shaposhnik (Российский кардиологический журнал, 2021)
Aim. In practice, to evaluate the efficacy, safety and long-term adherence to therapy with a fixed-dose combination of ramipril/indapamide (Konsilar-D24) in patients with grade 1-2 hypertension (HTN) who have not achieved blood pressure (BP) control with prior therapy or have not taken antihypertensive therapy.Material and methods. This multicenter open-label observational program included 524 patients with grade 1-2 HTN who did not take antihypertensive therapy or did not reach the target BP level with mono or dual antihypertensive therapy, as well as patients shifted to Konsilar-D24 therapy no later than two weeks before the start of the program. All patients signed a written informed consent to participate in the program. The safety analysis set includes all patients who have taken at least one dose of a fixed-dose combination of ramipril/indapamide and have visited physician at least once during the program. The effectiveness analysis set included all patients in the safety population who completed the study in accordance with protocol (n=511). Clinical systolic blood pressure (SBP), diastolic BP (DBP) and heart rate were assessed at baseline, as well as at 0,5, 1, 3 and 6 months of treatment. A post hoc subgroup analysis of changes in BP and heart rate was performed depending on age, sex and baseline body mass index.Results. The fixed-dose combination of ramipril with indapamide significantly reduced SBP and DBP after 2-week treatment (-20,9±10,1 mm Hg; pConclusion. Despite the limitations inherent in observational studies, the KONSONANS program has demonstrated high efficacy and safety of fixed-dose combination of ramipril/indapamide taken once a day in hypertensive patients. Ramipril/indapamide fixed-dose combination therapy significantly improved BP control and achieved even lower individual target BP levels in the majority of hypertensive patients.